2015
DOI: 10.1016/j.joms.2014.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Practices, and Opinions of Ontario Dentists When Treating Patients Receiving Bisphosphonates

Abstract: Background: Bisphosphonate related osteonecrosis of the jaws (BRONJ) is a severe but

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
50
4
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 47 publications
11
50
4
5
Order By: Relevance
“…In Ontario (Canada), Alhussain et al found 60% of the dentists interviewed to have adequate knowledge of bisphosphonate-related osteonecrosis. On the other hand, 50% of the professionals did not feel comfortable treating patients using bisphosphonates, and 23% claimed to follow the published guidelines referred to surgical treatment (8). …”
Section: Discussionmentioning
confidence: 99%
“…In Ontario (Canada), Alhussain et al found 60% of the dentists interviewed to have adequate knowledge of bisphosphonate-related osteonecrosis. On the other hand, 50% of the professionals did not feel comfortable treating patients using bisphosphonates, and 23% claimed to follow the published guidelines referred to surgical treatment (8). …”
Section: Discussionmentioning
confidence: 99%
“…Alhussain et al reported the opinions of dentists regarding the treatment of patients receiving BP; 60% of dentists had good knowledge of BRONJ, but most were not comfortable performing oral surgery in patients receiving BP, and 63% would refer patients if they were taking BPs. Only 23% of dentists followed the guidelines for surgical treatment of a patient taking BPs 24 . The discrepancy with guidelines reported in the previous study adds to the disagreement between dentists and practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…Our study was conducted in the city of Juiz de Fora, State of Minas Gerais, from June 2017 to January 2018. A self-applicable questionnaire was formulated based on the AAOMS updated position paper [12] and on the adapted questionnaire used by Alhussain et al [15]. Prior to data collection, the questionnaire was applied to two oral-maxillofacial surgeons for calibration in order to provide clarity and reliability to the collected data.…”
Section: Methodsmentioning
confidence: 99%
“…Alhussain et al assessed the knowledge of dentists and found that 60% showed a good level of knowledge on BP as they considered ONJ as a side effect, although they opted for referring the BP-treated patients. The authors concluded that although dentists demonstrated a good knowledge, the majority did not feel comfortable treating patients with ONJ [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation